Lagos' Bus Stop Names and their Pronunciations by Danfo Bus Conductors - Kenneth Obiorah (Masyarakat Linguistik Indonesia Universitas Andalas, 2021)
Danfo Buses are one of the main means of transportation in Lagos. For commuters to move from one location to another, it is highly essential that they know their bus stops and how the Danfo bus conductors pronounce them. This is because an inability to understand how these bus stops are pronounced will make it difficult for commuters to locate their destination. This paper aims to classify Lagos bus stop names based on their languages and sources of origin and demystify their pronunciation by Danfo bus conductors. Data was gathered through audio recordings of the speeches of the Danfo bus conductors. Data shows that bus stops in Lagos were named using both the local and English languages. Data also reveals that the names of these bus stops were derived from several ancient landmarks, including religious landmarks, commercial activities, agro-related landmarks, ancient edifices, and long-standing handiwork practices around these bus stops either now or in time past. The data further shows that the Danfo bus conductors employ various phonological processes such as vowel deletion, nasal deletion, vowel lengthening, consonant deletion, and word deletion in the pronunciation of bus stop names. The public is urged to take cognisance of these pronunciations in order not to miss their locations.